SOCIAL ENGINEERING ON SOCIAL MEDIA PLATFORMS: AN INTERDISCIPLINARY STUDY OF TECHNICAL DESIGN AND THE SHAPING OF ONLINE COLLECTIVE BEHAVIOR - Romi Mesra (ENGINTECH: Journal of Engineering and Technological Sciences, 2025)
This study aims to analyze the phenomenon of social engineering in social media platforms and its impact on the formation of online collective behavior through an interdisciplinary approach that combines the perspectives of digital sociology with engineering science. Social engineering in the digital context refers to the use of sociological, psychological, and communicative strategies integrated into the technical design of platforms to influence social structures, norms, and behavior on a massive scale. The research method uses a qualitative approach with a systematic literature review of 127 articles and academic books relevant to the topic of digital social engineering, analyzed using a thematic analysis approach to identify meaningful patterns and themes. The results reveal three main findings: first, social media platform algorithms operate as social agents that shape collective behavior through systematic mechanisms of algorithmic curation, viral amplification, and behavioral modification; second, platform architecture creates behavioral architecture through design features such as notification systems, gamification elements, and network structures that influence patterns of social interaction; third, digital social engineering has transformed the nature of collective behavior, creating new forms of social mobilization, digital inequality, and challenges to democratic discourse. This research provides theoretical contributions through the development of an interdisciplinary framework and a new typology of forms and mechanisms of digital social engineering, as well as practical implications for the development of more ethical platforms and appropriate policy frameworks for digital governance.